PERAN PEMERINTAH DALAM PERLINDUNGAN KONSUMEN TOKOPEDIA PADA PERKARA No. 235/PDT.G/2020/PN.JKT.PST. (Jurnal De Jure Muhammadiyah Cirebon, 2023)
In 2020 the Indonesian Consumer Community is suing the Minister of Communication and Informatics and PT. Tokopedia. In this case PT. Tokopedia stores and protects the confidentiality of personal data and the privacy rights of users of the online shopping site Tokopedia.com which are currently controlled by third parties without the consent of the account owner. In this problem the data controlled by P.T. Tokopedia has distributed as many as 106 million leaked data to third parties, causing offers to be made on the dark web for trading. This consumer data consists of email address, date of birth, gender, and telephone number. The spread of this information can lead to other cyber crimes. Furthermore, his personal data that is controlled by consumers has the potential for Cyber crimes in the form of (Scaming, Phishing, Malware) and other criminal acts.Keywords: Protection, Consumers, Cyber Crime.